2023
DOI: 10.1177/03331024231174160
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing opioid use in a Dutch cohort with migraine

Rein F van Welie,
Floor C van Welie,
Simone de Vries Lentsch
et al.

Abstract: Background There is lack of data on opioid (over)use for migraine in Europe. Methods We performed a cross-sectional study in a large Dutch cohort using a web-based questionnaire to assess opioid use in individuals with migraine. Primary outcome was to assess opioid use for the treatment of migraine attacks. As secondary outcomes we specified use of opioids (duration of use, type of opioids, prescriber) and compared between persons with episodic migraine versus chronic migraine. Descriptive statistics, unpaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Opioids are known to have no better efficacy than NSAIDs for treating migraine, and they are associated with higher rates of migraine recurrence and greater adverse effects, are potentially addictive, and are commonly implicated in medication overuse headache (MOH) [ 17 , 18 ]. Previous studies in many countries and regions have concluded that prescribing opioids for migraine attacks is common [ 19 , 20 ]. The 16% of opioid use suggests that opioid control remains inadequate, at least in migraine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are known to have no better efficacy than NSAIDs for treating migraine, and they are associated with higher rates of migraine recurrence and greater adverse effects, are potentially addictive, and are commonly implicated in medication overuse headache (MOH) [ 17 , 18 ]. Previous studies in many countries and regions have concluded that prescribing opioids for migraine attacks is common [ 19 , 20 ]. The 16% of opioid use suggests that opioid control remains inadequate, at least in migraine treatment.…”
Section: Discussionmentioning
confidence: 99%